Pengaruh Experiential Marketing, Daya Tarik Wisata, Citra Destinasi dan Fasilitas Wisata terhadap Kepuasan Pengunjung Kebun Raya - Sabila Nasuha; Supiani (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze the influence of experiential marketing, tourist attraction, destination image, and tourist facilities on visitor satisfaction at Bogor Botanical Gardens. The study uses a quantitative approach with primary data collected through a Google Form-based questionnaire and supported by secondary data from previous studies. The research period covers 2020–2024 with a population of all people residing in Greater Jakarta who have visited Bogor Botanical Gardens. The research sample consisted of 120 respondents determined using purposive sampling. Data analysis was performed using multiple linear regression with SPSS software, through instrument testing, classical assumption testing, t-test, F-test, and coefficient of determination test. The results showed that experiential marketing and tourist attraction had a negative effect on visitor satisfaction, while destination image and tourist facilities had a positive effect on visitor satisfaction at Bogor Botanical Garden.